2016
DOI: 10.1007/s00109-016-1447-7
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPβ regulates homeostatic and oncogenic gastric cell proliferation

Abstract: Cancer of the stomach is among the leading causes of death from cancer worldwide. The transcription factor C/EBPβ is frequently overexpressed in gastric cancer and associated with the suppression of the differentiation marker TFF1. We show that the murine C/EBPβ knockout stomach displays unbalanced homeostasis and reduced cell proliferation and that tumorigenesis of human gastric cancer xenograft is inhibited by knockdown of C/EBPβ. Cross-species comparison of gene expression profiles between C/EBPβ-deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 35 publications
0
23
1
Order By: Relevance
“…The identification and characterization of inhibitory compounds with this cell line has shown that candidate inhibitors affect MYB activity also indirectly by targeting the transcription factor C/EBPβ, a crucial co-operation partner required by MYB to induce MIM1 expression 28 31 . Although small-molecule inhibitors of C/EBPβ are also of interest given that C/EBPβ has pro-oncogenic roles in several tumors 32 36 , we wanted to be able to search for MYB inhibitors in a more focused manner. We therefore generated the reporter cell line illustrated schematically in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The identification and characterization of inhibitory compounds with this cell line has shown that candidate inhibitors affect MYB activity also indirectly by targeting the transcription factor C/EBPβ, a crucial co-operation partner required by MYB to induce MIM1 expression 28 31 . Although small-molecule inhibitors of C/EBPβ are also of interest given that C/EBPβ has pro-oncogenic roles in several tumors 32 36 , we wanted to be able to search for MYB inhibitors in a more focused manner. We therefore generated the reporter cell line illustrated schematically in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CCAAT/enhancer-binding protein β (C/EBPβ) is a member of the basic leucine zipper (bZIP) class of transcription factors and is involved in regulating cell growth, differentiation, inflammation, metabolism, survival, and tumorigenesis [1,2,3,4,5]. The growth-regulatory function of C/EBPβ has been reported to inhibit [6,7] or promote [8,9,10,11] cell proliferation, both in normal [6,8,9,10] and cancer cells [7,9,11]. For example, in C/EBPβ knock-out mice, hyperproliferation of epidermal keratinocytes was observed [6], but cell proliferation of B lymphocytes and gastric mucosa was decreased [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The growth-regulatory function of C/EBPβ has been reported to inhibit [6,7] or promote [8,9,10,11] cell proliferation, both in normal [6,8,9,10] and cancer cells [7,9,11]. For example, in C/EBPβ knock-out mice, hyperproliferation of epidermal keratinocytes was observed [6], but cell proliferation of B lymphocytes and gastric mucosa was decreased [8,9]. Thus, it is important to investigate how the function of C/EBPβ is determined in the cellular context and to determine what elicits these opposite growth responses including upstream regulators and downstream effectors.…”
Section: Introductionmentioning
confidence: 99%
“…C/EBPβ is overexpressed in human intestinal-type gastric cancers,26,27 human gastric cancer,28 ovarian cancer,29 colorectal cancer,30,31 etc. It promotes cell proliferation, invasion, migration and metastasis inhibits cell differentiation and apoptosis promotes inflammation, immune suppression, and pro-oncogenic functions 14,28,3133. Overexpression of C/EBPβ promoted cell invasive and migratory activity; downregulation of C/EBPβ suppressed malignant activities of 786-O cells.…”
Section: Discussionmentioning
confidence: 99%